2010
DOI: 10.4028/www.scientific.net/kem.436.157
|View full text |Cite
|
Sign up to set email alerts
|

Titanium and Titanium Alloy via Sintering of TiH<sub>2</sub>

Abstract: Blended elemental (BE) powder metallurgy (PM) is a promising low cost approach for manufacture titanium and titanium alloy components. Conventional BE method relies on sintering of pure titanium metal powder, while the new approach examined in this investigation produces bulk titanium materials by sintering titanium hydride powder. Dehydrogenation and densification of TiH2 powders with different particle sizes and TiH2-6Al-4V alloy powder was studied using thermogravimetric and dilatometric techniques. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 8 publications
3
19
0
Order By: Relevance
“…However, it should be noted that the ex-situ XRD and TEM investigations may suffer from instant information loss in terms of the phase transformation during the heating process [19,27,30,46,47]. Additionally, although in situ high temperature XRD and X-ray synchrotron/neutron diffraction techniques were applied, their results may still be of concern.…”
Section: Dehydrogenation Processmentioning
confidence: 99%
“…However, it should be noted that the ex-situ XRD and TEM investigations may suffer from instant information loss in terms of the phase transformation during the heating process [19,27,30,46,47]. Additionally, although in situ high temperature XRD and X-ray synchrotron/neutron diffraction techniques were applied, their results may still be of concern.…”
Section: Dehydrogenation Processmentioning
confidence: 99%
“…The use of hydrogenated Ti powder instead of metallic Ti powder has been shown to result in reduced oxygen content in the sintered alloy (see section 'Vacuum sintering TiH 2 ') [170,171]. Additionally, the brittleness of Ti hydride results in a tendency of the powder to crush during cold compaction [172,173]. This has been shown to result in better green density over Ti powder of similar particle size and morphology when using the same compaction pressures.…”
Section: Sintering Of Tihmentioning
confidence: 99%
“…Since 2011, a process called HSPT has been developed by Fang, Sun, and Paramore et al [4,172,174,[202][203][204][205][206][207][208][209][210][211][212][213] HSPT is a multi-step pressureless sintering process, in which Ti hydride or partially hydrogenated Ti powder is blended with master-alloy or elemental powders and sintered under a dynamically controlled hydrogen atmosphere. After sintering, residual hydrogen is removed by annealing under vacuum or inert gas ( Figure 21).…”
Section: Sintering Of Tih 2 In Hmentioning
confidence: 99%
“…As shown by review/overview articles, [1][2][3][4] the newly developed low cost titanium/titanium alloy powder production techniques such as the Armstrong and hydrogenation-dehydrogenation (HDH) processes in combination with PM processes will likely lead to cost effective production of titanium/titanium alloy bulk materials and near-net-shaped components. Wang et al [5] and Abakumov et al [6] showed that using titanium hydride (TiH 2 ) powder they can accelerate the sintering process of titanium and titanium alloy powders. Bolzoni et al [7] also showed that using HDH titanium powder it is more favorable than using titanium sponge fine powder in terms of mechanical properties.…”
Section: Introductionmentioning
confidence: 99%